EVALUASI PROGRAM PEMBELAJARAN SAINTIFIK - Fatimah, Nurul Suci; Bisri, Hasan; Ichsan, Muhammad (Universitas Djuanda, 2019)
One of the government's policies for the education sector that now must be implemented by every school is using the 2013 curriculum, especially for the elementary school level of education. There are many approaches that can be used in basic and secondary education. This study did at SDIT Raudlatul Jannah that has a learning program using a scientific approach. This research used qualitative approach by type of evaluation research with Stake Model. Data were collected through observation techniques, interviews, questionnaires, and documentation studies. Data analysis techniques were done through data reduction, display data, and verification. The result of the study showed that the context aspect (antecedent) base or implementation of learning program of scientific approach in SDIT Raudlatul Jannah is in line with the regulation of minister of education and culture No. 103 year 2014 article 2 verse 7. Transactional aspect of transaction evaluation of scientific approach in SDIT Raudlatul Jannah 85% has met the criteria. Output aspect based on average KKM's achievement, student's SME scores, and students' effective student-level outcomes are good.